Handbook of research on activating middle executives' agency to lead and manage during times of crisis - Wilmot, Ann-Marie, 1973-; Thompson, Canute S. (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"This book offers how to use empirical research in the area of leadership in times of crisis to provide leaders with the theoretical underpinning and practical applications tools and skills to equip middle leaders to meaningfully participate in crisis management and resolution in institutions for improved outcomes"--